Sculpting and fusing biomimetic vesicle networks using optical tweezers - Guido Bolognesi (Nature Portfolio, 2018)
Assembly of higher-order artificial vesicles can unlock new applications. Here, the authors use optical tweezers to construct user-defined 2D and 3D architectures of chemically distinct vesicles and demonstrate inter-vesicle communication and light-enabled compartment merging.